Analysis of Perception, Attitude, and Quality of Service on Patient Satisfaction at the Registration Place of the Kesambenkulon Health Center, Kediri - Kumalasari, Menik Tri; Katmini, Katmini (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2023)
Background: Understanding the patient's needs and wants is an important thing that affects patient satisfaction. The purpose of this study is to analyzethe influence of perceptions, attitudes and quality of service on patient satisfaction at the registration of the Kesambenkulon Health Center. Subjects and Method: A cross sectional study conducted at Kesambenkulon Health Center, from August 19 to September 4, 2022. A sample of 105 respondents was taken by a simple random sampling. The dependent variable was patient satisfaction. The independent variables are perceptions, attitudes and service quality. Data were analyzed using a multiple linear regression.Results: Perception (b= 0.23; 95% CI= 6.12 to 8.13; p<0.001), attitude (b= 0.43; 95% CI= 5.65 to 7.84; p= 0.002), quality service (b= 0.15; 95% CI= 4.84 to 7.59; p= 0.002) were significantly associated with patient satisfaction at the Kesambenkulon health center registration (adj. R2= 81.2%). Conclusion: The researcher believes that understanding the patient's needs and desires is an important thing that affects patient satisfaction. Satisfied patients are very valuable assets because if patients are satisfied they will continue to use the services of their choice.Keywords: satisfaction, service quality, perception & attitudeCorrespondence: Menik Tri Kumalasari. Masters Program in Public Health, Strada Indonesian Institute of Health Sciences. Jl. Manila 37, Sumberece. Pesantren, Kediri, East Java 64133, Indonesia. Email: meniktrikumalasari@gmail.com. Mobile: +6281235500034.Journal of Health Policy and Management (2023)https://doi.org/10.26911/thejhpm.2023.08.01.07